2017
DOI: 10.1186/s41824-017-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG-PET/CT texture analysis in thyroid incidentalomas: preliminary results

Abstract: Backgroundsignificance of incidental thyroid 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) uptake on positron emission tomography/computed tomography (PET/CT) scans remains controversial. We aimed to evaluate the ability of [18F]FDG-PET/CT texture analysis to predict final diagnosis in thyroid incidentaloma.MethodsWe retrospectively evaluated medical records of all patients who performed a [18F]FDG-PET/CT from January 2012 to October 2016. Those patients who presented a thyroid incidentaloma described in the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 32 publications
0
52
1
Order By: Relevance
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…Another PET TA of 50 patients with thyroid incidentaloma revealed that the skewness of thyroid malignancies was significantly lower than that of benign nodules, while kurtosis was not significantly different between groups. [ 35 ] In contrast, kurtosis and skewness were found to have no significant differences between the baseline and intra-treatment PET images in patients with non-small cell lung cancer. [ 36 ] In PET TA, due to the diversity of the tumor biological characteristics, especially the diversity of cellular FDG uptake, the application value of kurtosis and skewness fluctuates according to the tumor being studied.…”
Section: Discussionmentioning
confidence: 99%
“…When SUV max � 4.56 was undertaken as the best critical point for diagnosis, the sensitivity and specificity of SUV max for diagnosing the benign and malignant nodules was 81.33% and 76.18%, respectively. e results of Sollini et al [17] showed that the SUV max critical value for the diagnosis of benign and malignant TN was 5.0, and the corresponding diagnostic sensitivity and specificity was 60% and 91%, respectively. us, the sensitivity of SUV max in the diagnosis of the benign and malignant nodules had been significantly improved, but its specificity was decreased to a certain degree.…”
Section: Discussionmentioning
confidence: 99%